Long non-coding RNA 00960 promoted the aggressiveness of lung adenocarcinoma via the miR-124a/SphK1 axis - Zhipeng Ge (Taylor & Francis Group, 2021)
Long non-coding RNAs (lncRNAs) are closely associated with the development of lung adenocarcinoma (LADC). The present study focused on the role of LINC00960 in LADC. miRNA and mRNA expression levels were detected using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Cellular functions were evaluated by MTT, colony formation, and Transwell assays, respectively. LINC00960 Luciferase and RNA pull-down assays were performed to clarify the interaction between miR-124a and LINC00960 or Recombinant Sphingosine Kinase 1 (SphK1). We observed that LINC00960 was overexpressed in LADC tumor tissues and cell lines. LINC00960 knockdown suppressed the proliferation, migration, and invasion of LADC cells. Moreover, LINC00960 sponged miR-124a to inhibit the SphK1/S1P pathway in LADC cells. LINC00960 knockdown markedly reduced the rate of tumor growth. The luciferase reporter assay results demonstrated an interaction between miR-124a and LINC00960 or SphK1. This interaction was confirmed using the RNA pull-down assay. In addition, miR-124a downregulation or SphK1 upregulation reversed the inhibitory effects of LINC00960 knockdown on cellular functions of LADC cells, suggesting that LINC00960 may be a potential therapeutic biomarker for LADC via the miR-124a/SphK1 axis. Accordingly, LINC00960 may be a potential therapeutic biomarker for LADC.